إعادة الجدولة وإعادة الهيكلة للديون دراسة تحليلية شرعية = Rescheduling and restructuring of debt Shariah and analytical study - Muhamd Ruhni, Nur Nabilah; Saleh, Abdulmajid Obaid Hasan; Abdul Aziz, Akhtarzaite (IIUM Press, International Islamic University Malaysia, 2020)
من المشاكل التي تواجهنا في التعاملات المالية متأخرات الديون، فمن جهة المدين قد يكون أنه عاجز عن إتمام سداده وعنده ضيق في التدفق النقدي ومن جهة الدائن يقع في الخسارة بسبب متأخرات الديون. نظراً لتلك الطبيعة، ابتكرت المصارف بعض الوسائل لتدير مشكلة متاخرات الديون ومنها إعادة الجدولة وإعادة الهيكلة. تهدف هذه المقالة لبحث حقيقة عملية إعادة الجدولة وإعادة الهيكلة كوسيلة لاسترداد الديون كما تهدف لمناقشة الإطار الشرعي التأصيلي لهذه المسألة. يسعى هذا البحث لاستقصاء في بعض المراجع التي تبين حقيقة عملية إعادة الجدولة وإعادة الهيكلة وكذلك قلب الدين مع ذكر آراء الفقهاء المتقدمين والمعاصرين مع تعمق في القضايا الملحة في عملية إعادة الجدولة وإعادة الهيكلة. ********************************************************************************* One of the important issues in financial transactions is late payments. Each of the parties involved in the debt either the debtor or the creditor needs to address this problem. May be the debtor is unable to complete his debt payment and suffers a narrow flow of cash. While, the creditor faces possible losses arising from debt arrears. As a countermeasure, all banks have established mechanisms in managing the outstanding debt. These are known as rescheduling and restructuring. This research aims to examine the reality of rescheduling and restructuring as a debt recovery processes. This research looks also into the discussion of Qalb al Dayn as stipulated under Islamic law as debated among Muslim scholars. An aspect on the reality of the process of rescheduling and restructuring and Qalb al Dayn are also presented. As a result, it is found that one of debt recovery processes contains elements of Qalb al Dayn which may affect the determination of hukm.